Practical aspects of pediatrics and neonatology for nurses - Taksande, Amar (Jaypee Brothers Medical Publishers, 2014)
[This book] is an extremely thorough and comprehensive textbook. It presents the essential concepts that the nursing students need to know about the neonatal and pediatric procedures and their application. Also, it is designed to assist the nursing students in developing expertise and in-depth understanding in the field of pediatric nursing.